Defining more Roman amphora types from the Athenian Agora: too much history, too little typology (I) - Opaiţ, Andrei (Rei Cretariae Romanae Fautorum Acta, 2015)
Pontic and eastern Mediterranean sites have been excavated according to a strong art historical tradition, with investigators giving priority to monumental political and religious buildings, imposing mosaics and painted or relief decorated vessels. Although amphora studies have made good advances in these areas over the past few decades, we badly need to clarify the huge number of manufactured types, especially those of the late Hellenistic and Roman periods in the eastern Mediterranean area, giving a clear morphological and fabric definition of these vessels. In spite of the lack of excavation of production sites, a careful analysis of increasing information derived from consumption sites can help to elucidate the huge number of amphora types manufactured during these periods. We are still far from Keay’s desire “to select and address particular questions” and not to “become merely technicians who amass data.”